The Effect of Education Through Powtoon-based Learning Media on Balanced Nutrition Knowledge in Adolescents - Fikri Faidul Jihad; Darmawan Darmawan; Enda Silvia Putri; Maiza Duana; Hanif Muchdatul Ayunda; Muhibbul Subhi (Universitas Teuku Umar, 2023)
Several studies in Indonesia have utilized learning media to educate students. Nevertheless, no research looks at the effect of education through learning media on high school students about balanced nutrition using Powtoon, which is website-based. The research design used was a quasi-experimental one-group pretest-posttest design. The research was conducted at SMA Negeri 3 West Aceh Regency. Seventy-three respondents who met the inclusion criteria were selected. The results obtained a p-value of 0.000 (p < 0.05). Respondent's knowledge of balanced nutrition before being given education through Powtoon website-based learning media has a median value of 9 (5-12), and after the intervention, the median value rises to 13 (8 - 15). There is a significant difference in knowledge of balanced nutrition before and after the intervention. Therefore, learning with engaging media provides new experiences for students to understand the material presented. Powtoon learning media can be developed or compared with other learning media to find out which one is superior so that it can be widely used.